Effects of Ageing and Hearing Thresholds on Speech Perception in Quiet and in Noise Perceived in Different Locations - Mukari, Siti Zamratol-Mai Sarah (Korean J Audiol, 2014)
BACKGROUND AND OBJECTIVES: This study investigated the effect of ageing on speech perception in quiet and in noise, with noise directed from front, right and left. SUBJECTS AND METHODS: Sixty Malay native adults with normal or near normal hearing comprising of 20 young adults (21 to 39 years old), 20 middle aged (40 to 59 years old) and 20 older adults (60 to 74 years old) participated in this study. Their speech perception ability was measured using the Malay Hearing in Noise Test (HINT) in four test conditions; 1) in quiet (HINT Q), 2) with noise from front (HINT NF), 3) with noise from right (HINT NR), and 4) with noise from left (HINT NL). Reception thresholds for sentences (RTSs) were measured in each of the aforementioned conditions using an adaptive method. RESULTS: The results showed that, 1) genuine age-related decline was found in speech perception performance in HINT (NF), 2) hearing threshold was a major determinant differentiating speech perception performance for HINT (Q) and HINT (NL) conditions, and 3) speech perception performance for HINT (NR) was determined by both age and hearing threshold. CONCLUSIONS: This study suggests that, in older adults, while hearing thresholds affect speech perception in quiet, other factors such as central auditory processing and cognitive functions might be more important determinant factors for speech perception performance in noise.